2016
DOI: 10.18632/oncotarget.10567
|View full text |Cite
|
Sign up to set email alerts
|

Specific patterns of PIWI-interacting small noncoding RNA expression in dysplastic liver nodules and hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the result of a stepwise process, often beginning with development within a cirrhotic liver of premalignant lesions, morphologically characterized by low- (LGDN) and high-grade (HGDN) dysplastic nodules. PIWI-interacting RNAs (piRNAs) are small noncoding RNAs (sncRNAs), 23–35 nucleotide-long, exerting epigenetic and post-transcriptional regulation of gene expression. Recently the PIWI-piRNA pathway, best characterized in germline cells, has been identified also in somatic tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 56 publications
1
50
0
1
Order By: Relevance
“…By definition, piRNAs interact with PIWIL proteins, which we found in prostate . Recent small‐RNA sequencing studies of human somatic tissues have also detected hundreds of annotated or predicted piRNAs in ovary, liver, brain, and cell lines . The piRNAs identified in other human tissues share characteristics with the piRNAs we identified in prostate epithelium, such as a large portion mapping to introns and a weak or absent secondary piRNA biogenesis signature.…”
Section: Discussionsupporting
confidence: 56%
“…By definition, piRNAs interact with PIWIL proteins, which we found in prostate . Recent small‐RNA sequencing studies of human somatic tissues have also detected hundreds of annotated or predicted piRNAs in ovary, liver, brain, and cell lines . The piRNAs identified in other human tissues share characteristics with the piRNAs we identified in prostate epithelium, such as a large portion mapping to introns and a weak or absent secondary piRNA biogenesis signature.…”
Section: Discussionsupporting
confidence: 56%
“…As a methylation inducer, the impact of piRNAs during cancer development could be a consistent question. These later years, some works have profiled piRNA expression and explored their biological functions in cancer, including liver cancer [47,48]. In particular, piR-Hep1 was found to be upregulated in half of HCC tumors and piR-Hep1 silencing inhibited cell viability, motility, and invasiveness via a reduction of AKT phosphorylation.…”
Section: Piwirnasmentioning
confidence: 99%
“…In addition, piRNA is directly or indirectly involved in the formation of liver cancer. In 2016, Rizzo et al found that hsa_piR_013306 accumulates only in hepatocellular carcinomas (Rizzo, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%